2016
DOI: 10.1016/j.jtcvs.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of minimally invasive and standard aortic valve replacement

Abstract: Aortic valve replacement through a right anterior minithoracotomy surgery resulted in a reduced infection rate, diminished postoperative bleeding and blood transfusion requirements, reduced occurrence of new onset of atrial fibrillation, and shorter intensive care unit and hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 34 publications
1
47
1
1
Order By: Relevance
“…The main findings in this study are: (1) the early event rate of stroke after bioprosthetic SAVR was higher than previously reported; [1][2][3][4][5][6][7] (2) almost half of the strokes (44.4%) were of cardioembolic etiology; (3) preoperative atrial fibrillation was not associated with a higher risk of stroke or TIA; (4) approximately half of the patients with cerebrovascular events (47.2%) were on anticoagulation therapy at the time of the event.…”
Section: Main Findingsmentioning
confidence: 81%
See 1 more Smart Citation
“…The main findings in this study are: (1) the early event rate of stroke after bioprosthetic SAVR was higher than previously reported; [1][2][3][4][5][6][7] (2) almost half of the strokes (44.4%) were of cardioembolic etiology; (3) preoperative atrial fibrillation was not associated with a higher risk of stroke or TIA; (4) approximately half of the patients with cerebrovascular events (47.2%) were on anticoagulation therapy at the time of the event.…”
Section: Main Findingsmentioning
confidence: 81%
“…In previous registry-based studies, the incidence of stroke varied between 1.4% and 2.4% of patients during the in-hospital stay and between 6.1% and 13.8% during long-term follow-up. [1][2][3][4][5][6][7] Recent randomized studies, however, have suggested that in intermediate-risk patients the occurrence of stroke and TIA can already be as high as 6.5% within 30 days after surgery and 9.7% at 12 months. 8 This discrepancy may derive from register-based analyses, which are prone to an underestimation of the complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…Comment mAVR has been shown to offer clinical advantages [2], but it is associated with increased aortic cross-clamp time, which may in turn lead to increased morbidity [3][4][5][6][7]. Securing the valve prosthesis in a limited surgical field can be difficult, and automated suture devices have been developed to facilitate suture fastening.…”
Section: Resultsmentioning
confidence: 99%
“…Larger studies are needed to confirm the efficacy, safety, and cost-effectiveness of the CK device in minimally invasive aortic valve surgery. is gaining clinical acceptance with proven clinical outcomes [1] and potential advantages over the traditional sternotomy approach [2]. However, whether performed through a right thoracotomy or an upper sternotomy, minimally invasive valve procedures are associated with prolonged operative times because of the limited surgical field and restricted access [3].…”
mentioning
confidence: 99%
“…Although special anesthesiologic aspects have thus far not been studied in isolation, secondary endpoints-such as the length of stay in intensive care, the need for transfusion, and the rate of wound infections (5,26,27)-indicate differences in the administration of the anesthesia and in postoperative care. In our experience, for example, patients treated by using minimally invasive techniques are more suitable for early postoperative extubation.…”
Section: Anesthesia and Postoperative Care In Minimally Invasive Procmentioning
confidence: 99%